A new endogenous primate type C virus isolated from the Old World monkey Colobus polykomos. - Sherwin, S A (1979)
A new, genetically transmitted retrovirus has been isolated from the Old World monkey Colobus polykomos. This virus, designated CPC-1, is readily transmitted to both feline and human cells in culture. Nucleic acid hybridization studies reveal that there are 50-70 copies of the CPC-1 genome in colobus cellular DNA. Related virogene sequences can be detected in the DNA of all other Old World monkeys, as well as in the DNA of at least one ape species, the chimpanzee, indicating that this virus has been genetically transmitted in primates for 30-40 million years. CPC-1 is partially related to the type C virus previously isolated from stumptail monkeys (MAC-1). These two viruses have nucleic acid sequence homology, antigenic crossreactivity in their major viral structural protein, and a very similar host range in vitro. CPC-1 and MAC-1 therefore belong to the same class of genetically transmitted primate type C viruses and, as such, represent the first example in primates of analogous endogenous retroviruses isolated from two distantly related species.